Inhibiting electrochemical phase transition of NaCrO2 with long-cycle stability by surface fluorination treatment. (20th January 2022) - Wu, Jiahui; Hu, Guorong; Du, Ke; Peng, Zhongdong; Huang, Min; Fan, Ju; Gong, Yifan; Guan, Dichang; Shi, You; Liu, Ruirui; Cao, Yanbing
Abstract: The layered transition metal oxide of sodium-ion batteries (SIBs) has a high specific capacity and has been widely studied by scientific researchers. The O3 phase NaCrO2 (NCO) which is a kind of potential SIBs cathode material has good thermal stability and desirable safety performance. However, it suffers from complex phase transitions and rapid capacity decay during cycles. Herein, the robust dual-phase modification layer is construct on the surface of NCO to enhance its surface and interface stability. A dispersed pyrolytic carbon layer and the island LaF3 on the surface of the materials are formed by heat treatment of NCO with PVDF and La2 (CO3 )3 ·8H2 O. The effects of the modification amount on NCO structure, electrochemical performance and the capacity fading mechanisms are characterized by various methods. The results show that the surface fluorination modification not only helps to improve the conductivity of the surface of the materials by conductive carbon network and reduce the side reactions, but also enhances structural and interface stability by the stable LaF3 decoration and lattice oxygen replacement with pyrolysis of PVDF. It is worth noting that this modification method improves the thermodynamic stability of the electrode interface by introducing a highly stable coating on the electrode and it's beneficial to improve the rate performance and cycle performance of the material. As a result, the modified NCO displays good rate capability and cycle performance with 80.86% after 900 cycles at 2 C rate, and the specific capacity is 76.7 mAh g −1 at 40 C rate. This investigation highlights the advantages of this surface modification treatment method with respect to the surface stability of NCO and suppressing phase transition.